Caracterization of soils derived from quartzite with the aid of portable x-ray fluorescence (pXRF) spectrometry - Silva, Fernanda Magno (2019)
The variability of the elemental composition, the mineralogical and morphological characteristics of the soils derived from quartzite reflects the effects of the different factors of soil formation (climate, relief, parent material, organisms, time) and pedogenetic processes. Through portable X-ray fluorescence spectrometry (pXRF) and X-ray diffractometry (XRD) in air-dried and sieved samples as well as in the sand, silt, and clay fractions, this work was developed with the following objectives: to determine the elemental composition via pXRF as a tool to investigate the weathering degree and the pedogenic processes of soils developed from quartzite, besides correlating elementary data with soil physicochemical properties and to evaluate the concentration of the elements and its relation with the mineralogy of the sand, silt and clay fractions of soils with different degrees of weathering. In a toposequence, the horizons of five soil profiles were described and sampled: Lithic Ustorthent, Typic Ustorthent, Typic Dystrustept, Xanthic Hapludox, and Typic Udifolist. Laboratory analysis for soil physicochemical characterization of the air-died fine earth (ADFE) and separation of the sand, silt and clay fractions were performed. Both ADFE and the particle size fractions were analyzed with pXRF and only the fractions were analyzed mineralogically by XRD. Soils featured high contents of SiO2, with a higher amount present in the sand fraction due to the quartz, predominant in the quartzite and in the sand fraction of tropical soils. The Al 2O3 content was always higher in the clay fraction. K contents tended to be greater in the C horizons in the ADFE. Quartz, mica and kaolinite are the dominant minerals in the silt fraction. CaO and Sr were positively correlated with exchangeable contents of Ca 2+ and Mg 2+ , base saturation, pH, and cation exchange capacity. Fe, Al, Ti, Ca, K, Cu, Rb, and Zr accumulated in soil in comparison with the parent material. Variability of elemental contents in soils with different weathering and leaching degrees can be easily acc essed with pXRF and this equipment associated with the XRD enable to correlate the contents of the chemical elements to the minerals present in the soil particle size fractions.